Locality Reasoning Behind Kiai Sholeh Darat’s Thought In Majmūʻat Al-Syarīʻah Al-Kāfiyah Li Al-ʻawām - Irfan, Agus; Shidiq, Ghofar; Kuncoro, Anis Tyas (Proceedings of Annual Conference for Muslim Scholars, 2022)
A study of the works of Indonesian clerics, especially at the end of the 19th century was very dynamics. The discovery of local wisdom in the communication aspect is often found in the works of Indonesian scholars. In some cases, the archipelago aspect also influenced their intellectual works. For example, The book of fiqh entitled Majmūʻat al-Syarīʻah al-Kāfiyah li al-ʻawām by Kiai Sholeh Darat, was written using the coastal model of Javanese language (al-lughah al-Jawiyyah al-merikiyyah). Kiai Sholeh Darat's choice of the Javanese language as a means of communication became his literacy vision with the hope that the Javanese people at that time could understand and easily follow the message of the book. In addition to the language aspect, the local wisdom appears in the appearance and explanation aspects. Kiai Sholeh Darat chose to use the pegon script to interpret the book. Besides, in explaining the contents of the book, Kiai Sholeh Darat often provides examples of the issues discussed with several cases common in the public such as the Memule Dayang Merkayang, counting for "good day", Choosing market day, Nyahur tanah, Scales Size and so on.